Feasibility of the Montreal Cognitive Assessment in acute stroke patients. (12th July 2014) - Horstmann, S.; Rizos, T.; Rauch, G.; Arden, C.; Veltkamp, R.
<x xml:space="preserve">Abstract</x> Background and purpose Cognitive deficits are common following stroke. Cognitive function in the acute stroke setting is a predictive factor for mid‐term outcome. The Montreal Cognitive Assessment (MoCA) is a screening tool for cognitive impairment. The feasibility of MoCA in the acute phase of stroke was evaluated and factors predictive of cognitive impairment were determined. Methods In this prospective, single‐centre, explorative and observational study consecutive patients with ischaemic (IS) or haemorrhagic (ICH) stroke were enrolled between March 2011 and September 2012. The routine work‐up for each patient encompassed assessment of cardiovascular risk factors, the National Institutes of Health Stroke Scale (NIHSS) and the pre‐morbid modified Rankin Scale (mRS) score. Cognitive performance was measured using the German version of the MoCA within the first days of admission. A MoCA score of <26 was considered to indicate cognitive impairment. Results Between March 2011 and September 2012 a total of 842 patients with IS (89.0%) and ICH (11.0%) were enrolled in our study. MoCA was feasible in 678/842 patients (80.5%). Factors independently associated with non‐feasibility were stroke severity (NIHSS), pre‐morbid functional status (mRS), age and lower educational level. Mean MoCA was 21.4 (SD 5.7). A total of 498/678 (73.5%) patients appeared cognitively impaired (<26/30). Independent predictive factors for a lower MoCA score were age, educational level, stroke severity (NIHSS) and pre‐morbid functional status (mRS). Conclusions In the acute phase of stroke, MoCA is feasible in about 80% of eligible patients. At this stage, MoCA identifies a cognitive impairment in 75% of patients.